2009
DOI: 10.1080/18811248.2007.9711518
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Staggered Mesh for BWR Pin-by-Pin Core Analysis

Abstract: In this paper, the neutron current interpolation (NCI) method is proposed to treat the staggered mesh on the basis of the Simplified P3 (SP3) theory code. In the NCI method, the response matrix formulation is applied to the SP3 theory code, and neutron partial currents at assembly boundary are interpolated using low-order polynomial functions, i.e., flat, linear or quadratic function. The pin-by-pin fine-mesh core analysis method is considered as a candidate next-generation core calculation method for BWR. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, the number and the structure of energy groups, which are suitable for the pin-by-pin core analysis, have not been extensively investigated yet. For example, the validity of the 8-group structure used in the previous study for the BWR pin-by-pin core analysis is not fully confirmed [5,6]. Especially, in BWR, there is a significant variation of energetic and spatial distribution in neutron spectrum in a fuel assembly since BWR fuel assemblies have complicated geometries (e.g.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the number and the structure of energy groups, which are suitable for the pin-by-pin core analysis, have not been extensively investigated yet. For example, the validity of the 8-group structure used in the previous study for the BWR pin-by-pin core analysis is not fully confirmed [5,6]. Especially, in BWR, there is a significant variation of energetic and spatial distribution in neutron spectrum in a fuel assembly since BWR fuel assemblies have complicated geometries (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…In Equation (6), D is an index to represent the variation of neutron spectrum. The subscripts of i and g represent the mesh and the energy group indexes, respectively.…”
Section: Preservation Of Reaction Rates In a Single Assembly Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as a next generation core analysis method, the pin-by-pin fine mesh core calculation method for BWR core analysis has been studied [7,8]. The previous study indicates that the pin-by-pin approach for BWR core analysis has good accuracy to evaluate important parameters for highly heterogeneous cores (e.g., mixed-oxide (MOX) or high-burnup fuel loaded core).…”
Section: Introductionmentioning
confidence: 99%
“…In order to capture significant variation on energetic distribution of neutron spectrum in BWR fuel assemblies or in highly heterogeneous cores and to obtain higher prediction accuracy, utilization of finer energy group structure in core calculations is desirable. For example, eight-or nine-group structure is used in the previous study of the pin-by-pin approach for light water reactor core analysis [7][8][9]. However, even if we utilize such finer energy group structure, the spectral interference effect on the energy collapsing should be still taken into account and several correction techniques considering this effect are necessary.…”
Section: Introductionmentioning
confidence: 99%